The Loyal Customers' Perception Regarding the Online Buying Process - Claudia Bobalca (CES Working Papers, 2015)
The purpose of the research is to investigate the Romanian online customers' perception as regards to the process of buying products from the Internet. The research objectives are: (1) to identify the advantages and disadvantages of buying from the Internet; (2) to identify the reasons of buying from the Internet; (3) to identify the reasons of frequently buying from the same website. We employed a qualitative research method, based on depth interviews. It is an exploratory and instrumental research. The sample is represented by 30 Romanian online customers who frequently buy products from a specific website. The results show that the most important reasons for online shopping are: space accessibility, access convenience, evaluation convenience, delivery convenience, time saving and money saving. The motivations for repeating the purchase from the same website are: product quality, product diversity, quick delivery, easy to use, recommendations, good deals, safety, reputation and interactivity.
Keywords: M31; 330; loyalty; depth interview; online buying; advantages; disadvantages